THERE IS (NOT) SUCH THING AS WRONG RELIGION? (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2018)
After a millennium of great fights religion brought into civil society for primacy and supremacy, there is now an outstanding time of peace, of deliberation, of mutual listening for all religious partisans; and it really doesn’t matter what are the premises that has created such environment of dialogue [I have spoken about these preconditions in another conference1, emphasizing on the role civil society has in negotiating the conditions religion(s) have to obey in order to remain at the social table of disputing people’s attention].As a matter of fact, Religion(s) has to deal now – as they never did before – with a civil rule of getting along with all other religious manifestations, while developing internal leverages of mutual acceptance, a concept totally new and unprecedented. The concept is so new and often unbearable that members of any religious community are totally surprised by such steps and often resist to their heads who try to insinuate liberal practices and rules of acceptance of other religious beliefs. We cannot draw a genuine line of religiousness leading to errors and mistakes outdoors from a particular religion or denomination and leaving all other aside as wrong and ‘unwanted by gods’; how would we be certain and categorically about what god wants and how are his wishes to worship him?In the end, we have to see if there are such rational, moral, and theological prerequisites that give legitimacy to the functioning and free expression of the other religious factions, concurrent with the one in question; this is the main point of my paper here. I must state that this article has nothing to do with theological research of religion, but on an anthropological one.